Using Continuous Vital Sign Monitoring to Detect Early Deterioration in Adult Postoperative Inpatients. Issue 2 (April 2019) - Verrillo, Sue Carol; Cvach, Maria; Hudson, Krysia Warren; Winters, Bradford D.
Abstract : Background: Episodic vital sign collection (eVSC), as single data points, gives an incomplete picture of adult patients' postoperative physiologic status. Local Problem: Late detection of patient deterioration resulted in poor patient outcomes on a postsurgical unit. Methods: Baseline demographic and outcome data were collected through retrospective chart review of all patients admitted to the surgical unit for 12 weeks prior to this quality improvement project. Data on the same outcomes were collected during the 12-week project. Intervention: This project compared outcomes between the current standard of eVSC and the proposed standard of continuous vital sign monitoring (cVSM). Results: Using cVSM demonstrated a statistically significant 27% decrease in the complication rate, and a clinically significant decrease in transfers to an intensive care unit and failure-to-rescue (FTR) events rate. Conclusions: cVSM demonstrated detection of early signs of patient deterioration to prevent FTR. Abstract : Supplemental Digital Content is Available in the Text.